Developing a Validity Argument for an Inference-Making and Reasoning Measure for Use in Higher Education - Fechter, Tia; Dai, Ting; Cromley, Jennifer G.; Nelson, Frank E.; Van Boekel, Martin; Du, Yang (Frontiers in Education, 2021)
The Inference-Making and Reasoning in Biology (IMRB) measure is an assessment tool intended to (1) aid university personnel in advising students on course enrollment, (2) identify students in need of interventions to increase their reasoning skills and likelihood of completing STEM majors, (3) support instructors in determining growth in students’ reasoning skills, and (4) provide a measuring tool to gauge success of higher-education interventions intended to increase reasoning skills. Validity arguments for these four uses of the IMRB are provided by implementing a validity argument approach. This work exemplifies the advantages of framing validation studies within a validity argument framework.